Imperatives of Financial Intermediation to Economic growth - Babalola, Oladapo O. (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
Inter-sectoral transfer offunds has not been quiet efficient in the country overtime to aid growth and development. This study, therefore, examined the nexus between financial intermediation and economic growth in Nigeria, using data sourced from Central Bank of Nigeria (CBN) and World Bank database for variables spanning thirty three (33) periods on real gross domestic product (RGOP), a proxy for economic growth, commercial bank deposits (CBO), commercial bank credit (CBC), inflation at consumer prices and interest rate as indicators for financial intermediation. The OLS regression method and granger causality test was adopted to show the relationship that exists among RGOP as a dependent variable and all other variables as independent. Result shows that CBC and CBO exert a significant and positive impact on the economic growth of Nigeria while interest rate (INT) and inflation (INFC) , showed a negative relationship. The study, therefore, recommends that banks should reduce commissions and interests paid by customers on some bank transactions in order to encourage more patronage from them and as well endeavour that a major part of their credit is channeled to the important and productive sectors of the economy such as agriculture and manufacturing.